PENGARUH ANALISIS ELEMEN MODAL KERJA TERHADAP PROFITABILITAS ( ROI ) PADA PT. HANJAYA MANDALA SAMPOERNA , Tbk. - Musianah, Musianah; Amiranto, Jianto B. (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTThe Company was established with the aim to obtain operating profit. One way that can be done is to increase the profitability of the company. The company's profitability is influenced by a variety of financial factors which can be measured using financial ratios. The purpose of this study was to analyze the influence of the elements utuk rotation modes of work, namely perputran working capital, cash perputran receivable turnover and inventory turnover perusahanaan on profitability (Return On Investment) company. Population peneleitian is manufacturing companies listed in Indonesia Stock Exchange (BEI) is a renowned roko Company PT. HANJAYA MANDALA, Tbk. Samples used in this research are secondary data from reports keuanagan the period 2011 to 2015. The data obtained from the company's financial reports the official website of the Stock Exchange www.idx.co.id. And from the Indonesia Stock Exchange that are in UNIVERSITAS TUJUH BELAS AGUSTUS SURABAYA. Classical assumption test and multiple regression analyzes were performed using an SPSS version 22.0The results of this study indicate that the regression model is compliant with the study that there are no symptoms heteroskedastisitas, multikoliniearitas, and autocorrelation as well as the data used beristribusi normal. Regeresi multiple analysis results indicate that the F test, cash turnover , accounts receivable turnover, and inventory turnover significant effect on profitability (ROI). In test T cash turnover , receivables turnover and inventory turnover significant effect on profitability (ROI) Keywords: Cash Turnover , Accounts Receivable Turnover, Turnover supplies of , Profitability (ROI).